Pelatihan Relawan Pemeriksaan Hewan Kurban di Provinsi Lampung Tahun 2023 [Training of volunteer inspectors for sacrificial animals in Lampung Province in 2023] - Sirat, Muhammad Mirandy Pratama; Ermawati, Ratna; Farda, Fitria Tsani; Qisthon, Arif; Wanniatie, Veronica; Santosa, Purnama Edy (Universitas Syiah Kuala, 2024)
Lampung Province in 2022 ranked seventh nationally in beef cattle production with 906.6 thousand head and third in goat production with 1.67 million head, establishing itself as a key center for the provision of sacrificial animals. The training of volunteers in ante-mortem and post-mortem inspection of sacrificial animals aims to ensure the health of these animals. The sequence of outreach activities comprises five stages: 1) Administrative preparation; 2) Provision of training materials to volunteer inspectors; 3) Training in ante-mortem inspection of goats and cattle; 4) Training in post-mortem examination of goats; and 5) Evaluation of activities. The results from this community outreach initiative includes: 1) Training sessions and practical exercises in ante-mortem and post-mortem examination were attended by 104 volunteer inspectors in Lampung Province in 2023, resulting in a 10.55% increase in participants' knowledge from pre-activity (pretest) levels of 77.51% to 88.06% post-activity (posttest), categorized as high; 2) Ante-mortem and post-mortem inspections of sacrificial animals were conducted by 21 volunteer inspectors from 104 participants who took part in provision of training materials (20.19%) across seven districts/cities in Lampung Province; 3) A total of 535 sacrificial animals were inspected, comprising 242 cattle and 293 goats with Bandar Lampung City having the largest proportion of inspection sites. Conclusion of this activity there was an increase in the knowledge of sacrificial animal inspection volunteers after the training.